What Level Should Preoperative Albumin of Thoracic and Lumbar Tuberculosis Patients Be Reached: A Case-Controlled Study - Jiang, Guanyin; Zhu, Yong; Luo, Wei; Zhang, Wei; Qin, Wanyuan; Ou, Yunsheng (Frontiers in Nutrition, 2022)
Objective To explore the risk factors of hypoalbuminemia in patients with thoracic and lumbar tuberculosis and develop a scoring scale, according to which the patients with thoracic and lumbar tuberculosis were divided into 2 groups to, respectively calculate the perioperative albumin changes and to find out the preoperative albumin recommended value. Methods A total of 166 patients with thoracic and lumbar tuberculosis, who underwent spinal focus debridement between January 2012 to May 2020, were identified into 2 groups: with and without postoperative hypoalbuminemia (n = 131 and n = 35, respectively), recording and analyzing clinical characteristics by multivariate analysis to establish a scoring scale. Using this scale, patients with spinal tuberculosis were divided into a high-risk group and a low-risk group, and then, calculated the average decrease of postoperative albumin in both groups. Combined with the diagnostic threshold of hypoalbuminemia, we proposed the preoperative albumin safe values of the patients with thoracic and lumbar tuberculosis. Results A total of 131 of 166 patients experienced postoperative hypoalbuminemia after spinal focus debridement. Multivariate binary logistic regression analysis identified pulmonary tuberculosis (adjusted odds ratio = 0.270, p = 0.012), pre-operative serum albumin value (adjusted odds ratio = 0.754, p < 0.001), and operation time (adjusted odds ratio = 1.017, p = 0.002) as independent risk factors for the occurrence of postoperative hypoalbuminemia in patients with thoracic and lumbar tuberculosis. According to the OR value, the risk factors are assigned to make the scoring scale, the receiver operating characteristic (ROC) curve indicates that postoperative hypoalbuminemia rises when the score is greater than or equal to 4 points. The scoring scale is tested in the derivation set (166 patients) showed: sensitivity-51.9%, specificity-91.4%, and in the validation set (102 patients) showed: sensitivity-63.6% and specificity-86.1%. The perioperative albumin decreased value is 4.71 ± 2.66 g/L in the low-risk group and 8.99 ± 3.37 g/L in the high-risk group (p < 0.001). Conclusion Complicated with pulmonary tuberculosis, low preoperative albumin value and long operation time can lead to postoperative hypoalbuminemia in patients with thoracic and lumbar tuberculosis. The scoring scale can effectively assist physicians to evaluate whether patients with thoracic and lumbar tuberculosis develop hypoalbuminemia after surgery. The scale is simple and reliable and has clinical guiding significance. For low-risk patients and high-risk patients, preoperative albumin values should reach 40 and 44 g/L, respectively, to effectively avoid postoperative hypoalbuminemia.